2007
DOI: 10.1016/j.nucmedbio.2006.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-circulating liposomes radiolabeled with [18F]fluorodipalmitin ([18F]FDP)

Abstract: Synthesis of a radiolabeled diglyceride 3-[ 18 F]fluorodipalmitoyl-1,2-glycerol ( 18 F-fluorodipalmitin, [ 18 F]FDP) and its potential as a reagent for radiolabeling long-circulating liposomes were investigated. The incorporation of 18 F into the lipid molecule was accomplished by nucleophilic substitution of p-toluenesolfonyl moiety with a decay corrected yield of 43 ± 10% (n = 12). Radiolabeled long-circulating PEG-coated liposomes were prepared using a mixture of DPPC, cholesterol, DSPE-PEG2000 (61:30:9) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
1
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 35 publications
1
99
1
2
Order By: Relevance
“…With the exception of studies involving CRRRR, in all data reported here and in [25], activity in the bladder increased only after a delay of ~1000 seconds. With particles containing CRRRR, activity in the bladder increased immediately after injection of the particles, with this difference hypothesized to result from immediate cellular internalization of these particles or rapid extracellular enzymatic breakdown of the radiolabeled lipid.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…With the exception of studies involving CRRRR, in all data reported here and in [25], activity in the bladder increased only after a delay of ~1000 seconds. With particles containing CRRRR, activity in the bladder increased immediately after injection of the particles, with this difference hypothesized to result from immediate cellular internalization of these particles or rapid extracellular enzymatic breakdown of the radiolabeled lipid.…”
Section: Discussioncontrasting
confidence: 47%
“…Here, in order to facilitate high-resolution pharmacodynamic measurements, we employ 18 F for PET trafficking of peptide-targeted liposomes (Figure 1), using an 18 [25]. When free lipid is injected or the vehicle is recognized and metabolized by the RES, the 18 F-containing metabolite rapidly clears from the liver, facilitating real-time evaluation of the dynamics [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creation of a clinically-optimized ultrasound-enhanced drug or gene delivery vehicle is challenging due to the vast parameter space of potential materials, targeting ligands, cargos, and ultrasound parameters. We and others are developing cross-modality imaging methods in which nuclear medicine, magnetic resonance imaging, and optical imaging probes are used to visualize the delivery vehicle or the model drug [51][52][53][54].The great strength of nuclear imaging techniques, particularly positron emission tomography, is the real-time and highly sensitive full-body pharmacokinetics currently possible in pre-clinical studies [54,55]. Magnetic resonance imaging (MRI) techniques can be used to visualize the biodistribution of drugs or vehicles [52] and the activation of delivery vehicles in limited cases [51], and MRI can also be used to monitor local temperature in pre-clinical and clinical studies [56].…”
Section: Other Issuesmentioning
confidence: 99%
“…To prolong persistence of the therapeutic agent in vivo, polyethylene glycol-coated phospholipid liposomes have been designed that delay clearance from the circulation (Marik et al, 2007). Therapeutic nanocarriers are usually functionalized with biorecognition moieties on the surface such as peptides or antibodies to enable in vivo delivery of the therapy to the intended site such as the macrophage (Günther et al, 2011).…”
Section: Nanocarriersmentioning
confidence: 99%